Language learning strategies of future graduates for future employment: family influences - Abdul Kadir, Kadzrina; Wan Mohd Noor, Wan Shakizah; Abdul Rahim, Noor Fareen; Abdullah, Usry; Al-Arafati, Ahmed (Serials Publications, 2017)
English language fluency among graduates is becoming an important capability that graduates need for employment.The industry has noted the declining level of English among Malaysian graduates thus strategies and policies need to be implemented. Thus, how could teachers of non-English languages assist in increasing English language proficiency? This study looks at the issue of English language proficiency of business major students from the perspective of business lecturers, focusing on impact of family on student learning strategies. This study uses a qualitative method through interviews with two focus groups consisting of nine business major students. The students were interviewed on the importance of English language proficiency for future employment and the influence of family on their strategies to improve their English fluency. Family have important impact on the students’ strategies in improving their English fluency. The findings of this paper suggest that students with families with teachers or family members using English, may not necessarily have high awareness of importance of using English and suggest that self-motivation strategies play an important role, particularly when students are in their final year.